2017
DOI: 10.1007/s11004-017-9686-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Monitoring and Peat Assessment Using Multivariate Analysis of Regional-Scale Geochemical Data

Abstract: A compositional multivariate approach was used to analyse regional-scale soil geochemical data obtained as part of the Tellus Project generated by the Geological Survey of Northern Ireland. The multi-element total concentration data presented comprise X-ray fluorescence (XRF) analyses of 6862 rural soil samples collected at 20-cm depth on a non-aligned grid at one site per 2 km 2 . Censored data were imputed using published detection limits. Each soil sample site was assigned to the regional geology map, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…This case study, using a data set with relatively few components, is additional evidence that a simple approach to compositional data analysis is possible. Thus, other geochemical studies that have used the CLR transformation [62,64] would most probably have found almost identical results using a well-chosen ALR transformation -in particular, the study of the Tellus data in [64]. It is not claimed that this will always be the case, but sufficient successful applications have been found [48] to warrant considering the original approach of John Aitchison, using additive logratios, as well as alternative approaches that allow zero values, such as the power-transformed version of correspondence analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case study, using a data set with relatively few components, is additional evidence that a simple approach to compositional data analysis is possible. Thus, other geochemical studies that have used the CLR transformation [62,64] would most probably have found almost identical results using a well-chosen ALR transformation -in particular, the study of the Tellus data in [64]. It is not claimed that this will always be the case, but sufficient successful applications have been found [48] to warrant considering the original approach of John Aitchison, using additive logratios, as well as alternative approaches that allow zero values, such as the power-transformed version of correspondence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The cluster of points on the left represents peat, that is, soils that are highly enriched in organic material, chalcophile elements (S, Se, Cd, Pb), and lithophile elements (Cl, Br, I). The relative enrichment of I also reflects coastal effects associated with proximity to sea water [62]. To demonstrate the near isometry of the ALR transformation with Al as the reference, Fig.…”
Section: Comparing the Exact And Approximate Structuresmentioning
confidence: 99%
“…The study area is predominately made up of rocks of the Palaeozoic Southern Uplands-Down-Longford terrane (SUDLT), the Paleogene Slieve Gullion complex with younger intrusives and volcanic rocks to the north, west and east of the study area and Carboniferous sediments found to the south. The SUDLT, which extends across Scotland and Northern Ireland is dominated by Lower Palaeozoic marine sedimentary rocks (lithic arsenites and sandstones) which have undergone low-grade metamorphism (Steed and Morris 1986;Anderson 2004;Lusty et al 2012;McKinley et al 2017). The SUDLT bedrock is dominated by well-bedded Ordovician and Silurian turbidite sequences consisting of greywacke sandstone, siltstone and mudstone (Anderson 1 2004; Lusty et al 2012).…”
Section: Study Sitementioning
confidence: 99%
“…Subsequently, univariate statistical analysis (Filzmoser et al, 2009a), bivariate statistical analysis (Filzmoser et al, 2010;Reimann et al, 2017) and classical multivariate statistical analysis of compositional data (e.g. classification techniques, analysis of variance, linear discriminant analysis and spatial analysis, regression analysis, principal component analysis, factor analysis, clr-biplot and clustering of variables) have been proposed (Carranza, 2011(Carranza, , 2016Grunsky, 2010;Grunsky et al, 2014;McKinley et al, 2016aMcKinley et al, , 2016bMcKinley et al, , 2017Parent et al, 2014;Reimann et al, 2012;Thiombane et al, 2018;Tolosana-Delgado and McKinley, 2016;Wang et al, 2014). Moreover, the application of robust statistics (Carranza, 2016;Filzmoser et al, 2009b;Filzmoser et al, 2012b;Zuo, 2014), geostatistics (Grunsky et al, 2014;Pawlowsky-Glahn and Egozcue, 2016;Tolosana-Delgado and van den Boogaart, 2013;Tolosana-Delgado and van den Boogaart, 2014) and the use of fractal methods (Carranza, 2011) have all been applied in geochemical compositional data analysis .…”
Section: Introductionmentioning
confidence: 99%